A study on factors that increase customer value when conducting television shopping. (2016) - Fu, Hsin-Pin; Chang, Tien-Hsiang; Hsu, Kuei-Ying; Chen, Pei-Shiu
This study examined the factors that influence customer value in a TV shopping context. The fuzzy analytic hierarchy process (FAHP) was then applied to obtain the weights of these factors, and their importance was decided based on this. The results reveal that the top five important factors are as follows: payment security, private data security, commodity discount, short delivery time, and product usage security. Among these, payment security, private data security and product usage security are within the category of cost of security/safety. The results suggest that TV shopping operators should pay attention to their reputations in order to maintain a good corporate image and reduce doubts about security/safety. Meanwhile, logistics efficiency should be raised in order to shorten delivery times, and offering more discounts will act as an incentive to attract more shoppers and enhance customer value.